Foxtail millet [Setaria italica (L.) P. Beauv.] grown under nitrogen deficiency exhibits a lower folate contents - Wang, Yuan; Wang, Jin-song; Dong, Er-wei; Liu, Qiu-xia; Wang, Li-ge; Chen, Er-ying; Jiao, Xiao-yan; Diao, Xian-min (Frontiers in Nutrition, 2023)
Foxtail millet [Setaria italica (L.) P. Beauv.], as a rich source of folates, has been cultivated on arid infertile lands, for which N deficiency is one of the major issues. Growing environments might have a significant influence on cereal folate levels. However, little is known whether N deficiency modulates cereal folate levels. In order to obtain enriched folate foxtail millet production in nutrient-poor soil, we conducted a study investigating the content of folate derivatives of 29 diverse foxtail millet cultivars under two N regimes (0 and 150 kg N ha−1) for 2 years to explore folate potential grown under low N. The contents of total folate and most derivatives were reduced by N deficiency. The effect on total folate content caused by N was stronger than cultivar genotype did. Folate content of enriched folate cultivars was prone to be reduced by N deficiency. Structural equation models (SEMs) revealed that N fertilization had a positive indirect effect on grain folate content through influencing plant N and K accumulation. Collectively, the results indicate much more attention should be paid to N management when foxtail millet is cultivated in infertile soil, to improve foxtail millet folate contents.